Tradisi Attumate Masyarakat Desa Lakatong Kecamatan Managarabombang Kabupaten Takalar - Nining Miranti; Amal Arfan; Ibrahim Abbas (UNM Geographic Journal, 2020)
This research is a qualitative ethnographic study that aims to find out the procession of implementation, the meaning and the factors that lead to the survival of the Attumate Tradition. The research data were collected based on the results of observations, documentation, and interviews with selected informants using the Purposive Sampling technique. Data analysis was performed by data reduction, data presentation, and drawing conclusions. The Attumate tradition is a death ceremony carried out by the family of a deceased person, where the process starts with Ammuntuli, Ni Je'ne, A'roko, Angnyambayangngi, Soso’ Kalibong, Ammaca Talakking, Ammaca Kanre, Angngaji-Aji, Allo Parallu, Allo Biasa and Appalappasa Allo. Attumate tradition has the meaning of alms and friendship which is useful for praying for someone who has died. Lakatong Village community believes that by carrying out traditions that have long been the custom of ancestors, it will facilitate the journey of someone who has died to the end of nature. Attumate's tradition still survives because of the still strong influence of Sayyid in Lakatong Village which is spread along the coast of Lamangkia to Laikang and Lakatong Village community still considers that this tradition is a family pride that must be fought for so it must be implemented.